Urban sustainability through environmental design : approaches to time-people-place responsive urban spaces - Thwaites, Kevin (London ; New York : Routledge, 2007)
What can architects, landscape architects and urban designers do to make urban open spaces, streets and squares more responsive, lively and safe? This title answers this question by providing the analytical tools and practical methodologies that can be employed for solutions to the design and management of urban environments.
Space and people: the case for socially sustainable urban design -- Three core messages, or what we mostly should do -- The knowledge of order and complexity -- The beauty of order and complexity -- The building of order and complexity -- Cultural biases and disciplinary contradictions against time-conscious urban design -- Notices of time-conscious urban design: practices and projects -- Analytical techniques for a sustainable city -- Travel time budgets as a tool for sustainable urban design / Peter Newman -- The generation of diversity: mixed use and urban sustainability / Graeme Evans and Jo Foord -- Multiple centrality assessment: mapping centrality in networks of urban spaces / Sergio Porta and Vito Latora -- Measuring the success of transit-oriented development using a sustainability framework: TOD outcome analysis / John L. Renne -- Accessibility and user needs in transport: street audit toolkit / Nastaran Azmin-Fouladi -- Raster cities: image-processing techniques for environmental urban analysis / Eugenio Morello and Carlo Ratti -- Communities in Action Handbook / Ombretta Romice and Hildebrand Frey -- Collaborative planning and design for a sustainable neighbourhood on Quebec City's university campus / Genevieve Vachon ... [et al.] -- GIS behaviour mapping for provision of interactive empirical knowledge, vital monitoring and better place design / Barbara Golicnik -- Experiential landscape: revealing hidden dimensions of people-place relations / Kevin Thwaites and Ian Simkins -- Listening to and understanding the voices of people with learning disabilities in the planning and design process / Alice Mathers -- Listening to and understanding the voices of young children in the planning and design process / Ian Simkins
Includes bibliographical references and index.
ARC
Keywords: City planning; City planning -- Environmental aspects; Sustainable development; Public spaces